2019
DOI: 10.1002/ijc.32417
|View full text |Cite
|
Sign up to set email alerts
|

Impact of single‐nucleotide polymorphisms in DNA repair pathway genes on response to chemoradiotherapy in rectal cancer patients: Results from ACCORD‐12/PRODIGE‐2 phase III trial

Abstract: We examined whether 66 germline single-nucleotide polymorphisms (SNPs) in 10 candidate genes would predict clinical outcome in 316 patients with resectable locally advanced rectal cancer (LARC) enrolled in the ACCORD-12 phase III trial who were randomly treated with preoperative radiotherapy plus capecitabine (CAP45; n = 155) or dose-intensified radiotherapy plus capecitabine and oxaliplatin (CAPOX50; n = 161). The primary endpoint was tumor response according to the Dworak score. Multivariate logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Clinical studies have found that different individuals with the same clinical characteristics show great heterogeneity in clinical manifestations, treatment sensitivity, disease recurrence, and survival outcomes. We have previously reported on individual differences in genetic susceptibility, (31)(32)(33). However, a large number of research results are inconsistent, and there is no consensus on whether differences in DNA repair gene expression can be used as prognostic indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have found that different individuals with the same clinical characteristics show great heterogeneity in clinical manifestations, treatment sensitivity, disease recurrence, and survival outcomes. We have previously reported on individual differences in genetic susceptibility, (31)(32)(33). However, a large number of research results are inconsistent, and there is no consensus on whether differences in DNA repair gene expression can be used as prognostic indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Sixtysix germline SNPs were found in 10 candidate DNA repair genes. Boige et al [31] concluded that 5 SNPs located in ERCC1, MTHFR, excision repair cross-complementing group 2 (ERCC2) and XPA were closely related to the Dworak score. XPA rs3176683 was valuable for predicting the response to nCRT, while the ERCC2 rs1799787 and ERCC1 rs10412761 variants were reported to be promising prognostic markers.…”
Section: Single-nucleotide Polymorphisms (Snps)mentioning
confidence: 99%
“…A study carried out in 126 patients with advanced CRC, treated with a first-line oxaliplatin/5-FU chemotherapeutic regimen, showed that rs11615 and rs13181 SNPs were significantly correlated with clinical response and OS [ 134 ]. Patients with the T/G haplotype of the ERCC2 rs1799787 (c.1832-70C > T) and ERCC1 rs10412761 (c.-22 + 1089T > G) SNPs had a 60% decrease in odds of response to preoperative capecitabine and oxaliplatin-based chemoradiotherapy in locally advanced rectal cancer [ 135 ]. ERCC5 polymorphisms at the promoter region (c.-763A > G (rs2016073) and c.25G > A (rs751402)) may also be predictors of response to oxaliplatin-based chemotherapy in advanced CRC, as patients with the -763A/+25G haplotype had a higher risk of non-response to this pharmacological regimen [ 136 ].…”
Section: Dna Repairing (Moc-4)mentioning
confidence: 99%